Increasing use of digital technologies in function of economic growth in European countries - Valentina Mucunska Palevska; Blagica Novkovska (UTMS Journal of Economics, 2021)
Impact of the Information and Communication Technologies (ICT) on economic growth, recently attracted high research intererst. Thus, it has been found that in the case of developed European economies the considered impact is significant. In general, ICT diffusion has significant impact on the economic growth in high-income countries while smaller effect is observed in middle-income and low income countries. In the present work we study multiple aspects of the impact of ICT as a factor of the economic growth of European countries, both EU-28 and candidate countries. The internet usage across the regions is discussed in details. Social networking, online banking, e-government and e-commerce aspects are considered separately. Values for EU-28 are compared with these for Republic of North Macedonia, Montenegro, Serbia, Albania and Turkey. Digital gap between the elderly persons urban and rural areas is also studied. Rather low presence of online banking in some countries outside of EU-28 has been found. Based on analyses following recommendations are made: to create policies to shape the digital single market; to improve the digital infrastructure in North Macedonia, Montenegro, Serbia, Albania and Turkey; to bridge the digital divide between urban and rural areas.
Keywords: L86; O14; O33; 330; e-Business and Competitive Strategy; Information and communication technologies